Cryogenics in Renewable Energy Storage: A Review of Technologies - Arian Semedo; João Garcia; Moisés Brito (Energies)
The increase in the exploration of renewable energy sources intensifies the need for efficient storage solutions to mitigate the inherent intermittence of these sources. Among the available technologies, cryogenic energy storage (CES) systems stand out as a major and promising technology due to their high scalability, energy efficiency, and potential for integration with other systems. This paper deals with cryogenic approaches, focused on Liquid Air Energy Storage (LAES). Several topics are addressed, including the characterization of the CES systems, their working principle, with special relevance to efficiency and temperature/entropy diagram, the conception and the technical challenges, design, and construction of CES. LAES demonstrates energy efficiencies ranging from 45% to 70%, potentially reaching up to 75% with the integration of complementary technologies, with capital costs ranging from 900 EUR/kW to 1750/EUR/kW. Carbon dioxide (CO2)-based systems, while more energy-efficient (40% to 60%), face significant barriers due to high infrastructure costs. Additionally, hybrid configurations that combine advanced thermal cycles and waste heat management achieve efficiencies between 55% and 80%, showing adaptability in complex energy scenarios. In comparison with alternatives such as batteries and Compressed Air Energy Storage (CAES), despite economic and technological limitations, CES systems have a promising role in the global energy transition, particularly with anticipated advancements that will enhance their competitiveness and economic viability.